VIGOR BENIH KAKAO (Theobroma cacao L.) PADA BERBAGAI LAMA PENYIMPANAN DAN INVIGORASI - Maemunah Maemunah; Enny Adelina; I.Y. Daniel (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research aims were to determine the cocoa seed vigor of various storage periods and seed invigorant viewed from aspect of seed physiology quality. This research was a two factorial experiment in a completely randomized design. The first factor was the time length of storage consisted of 5 levels: i) Control, ii) 2 week, iii) 4 weeks, iv) 6 weeks, and v) 8 weeks. The second factor was seed invigoration using ZPT consisted of 4 types: i) without ZPT, ii). 0.01 mmol GA3, iii) 0.01 mmol GA3 + 0.1 mmol NAA, and iv) coconut milk. The data obtained was analyzed using variant analysis; the data with coefficient of variation more than 20 % was transformed to x + 0.5 whereas treatment with significant influence was advanced with HSD test with level of 0.05. The research findings showed that a longer period of seed storage led to the reduction of seed vigor. Invigoration with GA3 + NAA also contributed to a better seed vigor though it was not significantly different from GA3 invigoration and coconut milk. All seed invigoration treatment (GA3 + NAA and coconut milk) could slow seed deterioration up to 6 week storage.